ANALISIS PERHITUNGAN PAJAK PENGHASILAN 21 BERDASARKAN UU HARMONISASI PERATURAN PERPAJAKAN NO. 7 TAHUN 2021 ATAS UPAH TENAGA KERJA LEPAS GUNA MENENTUKAN PPh TERUTANG BADAN (STUDI KASUS CV. SUMBER REJEKI RINGINREJO) - Tri Agustin Widya Sari; Akhmad Naruli; Khasanah Sahara (Cahaya Ilmu Bangsa, 2025)
Tax is a mandatory contribution to the state owed by individual or corporate taxpayers which is coercive based on the law. The calculation of Income Tax Article 21 is carried out by the company so that it can pay as little tax as possible to the state. In calculating Income Tax Article 21, it can be done using three methods, namely Net, Gross and Gross Up. The aim of this research is to find out the most profitable method for calculating Income Tax Article 21 for CV. Ringinrejo's Source of Fortune. CV Sumber Rejeki Ringinrejo is a company operating in the manufacturing sector. The scope of this research is Analysis of Income Tax Calculation 21 based on the Law on Harmonization of Tax Regulations No. 7 of 2021 on Wages of Casual Workers to Determine Corporate Income Tax Payable in 2022. In this research, the type of research used is quantitative descriptive. The data source in this research is primary data from the company. The types of data in this research are qualitative data and quantitative data using interview and documentation data collection techniques. The results of the research and discussion show that calculating Income Tax Article 21 using the Gross Up method will have the greatest impact on saving Corporate Income Tax Payable compared to the Net method and Gross method, because Income Tax Article 21 of employees can be charged as a fiscal expense. Keywords: Income Tax Article 21, Net Method, Gross Method, Gross Up Method, Corporate Income Tax Due